Medical Device Research & Innovation - Status Quo, Challenges & Opportunities to Drive Global Healthcare Innovation (Transactions on Additive Manufacturing Meets Medicine, 2025)
Stryker is a global MedTech company that is driven to make healthcare better together with their customers. In this presentation, I will share insights on the novel strategic approach on innovation road mapping at Stryker to align technological advancements with business goals, enabling research to anticipate and navigate future challenges. This three-dimensional innovation process plays a crucial role in identifying emerging trends, regulatory changes, and market demands. By incorporating forefront research, this disruptive methodology ensures to remain at the cutting edge of innovation, from device design to regulatory approval and commercialization. The three-dimensional innovation process fosters collaboration across multidisciplinary teams, driving R&D investments, and ensuring that products meet both patient needs and business needs. Through collaborations with academic institutions, patient advocacy groups, industry forums, and cross-sector partnerships, I will share insights on challenges, risks, and successes from an industry perspective on the potential and future of 3D printed biodegradable patient-specific implants.
Keywords: Medical Devices; 3D printing; healthcare; Innovation